Analysis of Metabolites and Gene Expression Changes Relative to Apricot (Prunus armeniaca L.) Fruit Quality During Development and Ripening - García-Gómez, Beatriz Ester; Ruiz, David; Salazar, Juan Alfonso; Rubio, Manolo; Martínez-García, Pedro José; Martínez-Gómez, Pedro (Frontiers in Plant Science, 2020)
Apricot (Prunus armeniaca L.) is a valuable worldwide agronomical crop, with a delitious fruit highlighted as a functional food with both nutritional and bioactive properties, remarkably beneficial to human health. Apricot fruit ripening is a coordinated developmental process which requires the change in expression of hundreds to thousands of genes to modify many biochemical and physiological processes arising it characteristic quality characteristics in ripe fruit. In addition, enhance fruit and nutraceutical quality is one of the central objectives to be improved in the new varieties developed by breeding programmes. In this study we analyzed the contents of main metabolites linked to nutraceutical value of apricot, together with the most important pomological characteristics and biochemical contents of fruit during the ripening process in two contrasted apricot genotypes. Additionally, the gene expression changes were analyzed using RNA-Seq and real time qPCR. Reference mei, peach and apricot genomes and transcriptomes were simultaneously used as reference sequences for read analyaisis and mapping our candidates genes. However, for functional candidate gene analysis, studies were focused on mei and apricot reference genomes. Results showed as genes with differential expression in the biosynthetic pathways such as phenylpropanoids, flavonoids, starch and sucrose and carotenoids metabolism could be possible candidates as molecular markers of fruit quality characteristics for fruit colour and soluble solids content. The gene involves in carotenoid metabolism carotenoid cleavage dioxygenase 4, and the gene sucrose synthase in starch and sucrose metabolism were identified as candidate genes in the ripening process for white skin ground colour and flesh colour and high soluble sugar content. The application of these candidate genes on marker-assisted selection in apricot breeding programmes may contribute to the early selection of high-quality fruit genotypes with suitable nutraceutical values.